THE POLICY OF WORKING PERSONNEL MOVEMENT FROM THE TERRITORY OF THE USSR TO THE UZBEKISTAN SSR IN THE 1950-1960 - Amirdinov Jahongir Abdumajidovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
When considering this issue, which is "the policy of moving workers from the territory of the USSR to the Uzbekistan SSR in the 1950s and 1960s," in particular the internal and external labor policies of the Soviet government and the improvement of personnel quality, it was determined that it was necessary to examine the historical and statistical sources of their transformation. Consequently, this article addresses the potential of our country's industry personnel and their migration.